Diversity and management of Telangana goats maintained under field conditions - NK Verma; RAK Aggarwal; Rekha Sharma; PS Dangi (Journal of Livestock Biodiversity, 2025)
Goats of Telengana state which have the origin of Mahbubnagar district are also locally known as Mahbubnagari or Palamoor goat. Here, goats are reared mainly by SC/ST communities having no or little land holdings. Goats are kept under semi-extensive management sending them for pasture/jungle grazing during day time and at home in the night. Goat houses are temporary structures without any proper arrangement of water and electricicity Data were recorded on 207 animals of different age groups from farmers' flocks existed in different districts of the state. These goats are hardy, prolific and evolved due to natural selction in high tempertature climatic conditions of foot hills of Nallamala forest. It is known for fast growth rate and high prolificacy (50% twining, 20% triplets & quadruplets), low age of first kidding and short kidding interval. They are medium sized, leggy animals with varied coat colour i.e. white, black, brown, spotted, splashed, admixtures of black &brown, black and white, black & brown etc. Majority of animals had straight head, slightly convex head profile, pendulous ears, straight or backwardly curved horns. Wattles and beard are present in some animals of both sexes. To search the homogeneity in the population, the animals were broadly categorized into two, solid black and the mixed colour goats. The average body measurements (in cm) of adult mixed colour male goats for height, length, chest girth, paunch girth face length, horn length, ear length, tail length were 73.48±1.09, 67.13±1.19, 80.0±1.35, 79.26±1.50, 18.35±0.41, 13.96±1.20, 13.83±0.36, 13.35±0.42 respectively; for females 70.53±0.52, 67.22±0.51, 80.45±0.60, 81.45±0.71, 18.44±0.20, 13.88±0.42, 11.34±0.58, 13.37±0.23, The body weights were 38.70±1.91, 37.69±0.68 kg. The measurements for same traits in black male goats were 72.18±1.37, 65.27±1.13, 78.73±1.73, 79.64±1.78, 16.82±0.62, 12.56±1.14, 14.36±0.41, 14.09±0.46; for females, 72.03±0.77, 68.03±0.77, 81.31±0.69, 83.72±1.05, 18.17±0.26, 13.36±0.74, 12.42±0.83, 13.97±0.37cm and body weights were 37.27±2.52 and 40.42±1.02 kg. Breeding is through natural mating. These goats have early maturity and give multiple births (60% twining) second kidding onward. The results indicated that two groups of Telangana goats formed on the basis of coat colour were not distinct genetically and thus make a single population with lot of phenotypic heterogeneity.